Construction and validation of the Forgiveness Scale (VAPPER 490) - Aranda, Jessica (2016)
The objective of this study was the construction and evaluation of the psychometric properties of an instrument that assesses the ability to forgive in youth and adults between 20 and 35 year old. For this purpose, in the first stage of the study was realized the conceptual delimitation of the construct and was developed the preliminary instrument (42 items) based on the review of the literature concerning forgiveness. In the second stage, was considered a Pilot experiment of 150 youth and adults, where the exploratory factor analysis was performed in order to undergo a rigorous analysis of theoretical and dimensional nature of the construct. Also, the Cronbach’s alpha coefficient for both the dimensions and the global scale was obtained. It is concluded that the instrument demonstrates good internal consistency and construct validity